2023
DOI: 10.1002/pld3.516
|View full text |Cite
|
Sign up to set email alerts
|

Identifying developmental QTL alleles with favorable effect on grain yield components under late‐terminal drought in spring barley MAGIC population

Abstract: Barley is the fourth most cultivated cereal worldwide, and drought is a major cause of its yield loss by negatively affecting its development. Hence, better understanding developmental mechanisms that control complex polygenic yield‐related traits under drought is essential to uncover favorable yield regulators. This study evaluated seven above‐ground yield‐related traits under well‐watered (WW) and late‐terminal drought (TD) treatment using 534 spring barley multiparent advanced generation intercross double h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 78 publications
0
0
0
Order By: Relevance
“…GWAS have been used to investigate agro-physiological important traits in barley (Afsharyan et al 2023;Elbasyoni et al 2022;Li et al 2022;Thabet et al 2020;Wehner et al 2016a, b;Wehner et al 2015;Wójcik-Jagła et al 2018;Xiong et al 2023), but the presence of a high false positive rate result was the major challenge (Tibbs Cortes et al 2021). Beside the application of different p-values correction methods like FDR (Benjamini and Hochberg 1995) and Bonferroni methods, different GWAS models were developed to improve the computational power and efficiency.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…GWAS have been used to investigate agro-physiological important traits in barley (Afsharyan et al 2023;Elbasyoni et al 2022;Li et al 2022;Thabet et al 2020;Wehner et al 2016a, b;Wehner et al 2015;Wójcik-Jagła et al 2018;Xiong et al 2023), but the presence of a high false positive rate result was the major challenge (Tibbs Cortes et al 2021). Beside the application of different p-values correction methods like FDR (Benjamini and Hochberg 1995) and Bonferroni methods, different GWAS models were developed to improve the computational power and efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Candidate genes associated with drought tolerance that influence grain yield and associated traits (Li et al 2022), and drought triggered environmental signals (Elbasyoni et al 2022) were also reported. Post flowering drought experiment also revealed QTLs influencing drought tolerance in barley (Afsharyan et al 2023).…”
Section: Introductionmentioning
confidence: 96%